2017
DOI: 10.1017/inp.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Kentucky Bluegrass with Herbicide and Burning Is Influenced by Invasion Level

Abstract: Kentucky bluegrass (Poa pratensis L.) invades northern Great Plains rangelands. On the Sheyenne National Grassland in southeastern North Dakota, three research sites, each with a different level of Kentucky bluegrass invasion, were chosen to evaluate effectiveness of burning and burning–herbicide combinations to control Kentucky bluegrass. Initial Kentucky bluegrass invasion levels were 37%, 77%, and 91% for LOW, MODERATE, and HIGH invaded sites, respectively. Within each invaded site, four replicated strips (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Based on available evidence, it is reasonable to argue that the effectiveness of such control methods or treatments would depend on the degree of invasion. For example, Ereth et al (2017) recently reported that both herbicide and burning can help in controlling Kentucky bluegrass ( Poa pratensis L.) invasion, but the outcome depends on its level of invasion. Poa pratensis and smooth bromegrass ( Bromus inermis Leyss.…”
Section: Management Of Invasive Speciesmentioning
confidence: 99%
“…Based on available evidence, it is reasonable to argue that the effectiveness of such control methods or treatments would depend on the degree of invasion. For example, Ereth et al (2017) recently reported that both herbicide and burning can help in controlling Kentucky bluegrass ( Poa pratensis L.) invasion, but the outcome depends on its level of invasion. Poa pratensis and smooth bromegrass ( Bromus inermis Leyss.…”
Section: Management Of Invasive Speciesmentioning
confidence: 99%
“…Additionally, native species cover was also significantly greater under alternative grazing treatments. Application of herbicide, such as glyphosate, is a popular rangeland management practice [ 31 , 32 ]. In the NGP, the combination of burning and glyphosate application during early spring and late fall when the warm season grasses were dormant showed promising results in combating Kentucky bluegrass while increasing the native grasses [ 32 ].…”
Section: Requirement Of Efficient Management Strategiesmentioning
confidence: 99%
“…Application of herbicide, such as glyphosate, is a popular rangeland management practice [ 31 , 32 ]. In the NGP, the combination of burning and glyphosate application during early spring and late fall when the warm season grasses were dormant showed promising results in combating Kentucky bluegrass while increasing the native grasses [ 32 ]. Thus, alteration in traditional practices could be a potential strategy to control the Kentucky bluegrass invasion while improving the overall native species cover.…”
Section: Requirement Of Efficient Management Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…8,23 Even so, past studies in the northern Great Plains have found prescribed fire can reduce the cover of Kentucky bluegrass. [24][25][26] For example, Kral et al 26 found that burning in May, September, or November resulted in reduced Kentucky bluegrass cover and increased plant species diversity. After September prescribed fires, reduced Kentucky bluegrass cover persisted for at least 3 years, while cover increased to pre-fire levels after 1 year following May burning.…”
Section: Prescribed Firementioning
confidence: 99%